THE EFFECT OF COMPENSATION, WORKLOAD AND ORGANIZATIONAL COMMITMENT ON THE PERFORMANCE OF NON-ASN STATE HIGH SCHOOL TEACHERS IN BATAMCITY WITH ACHIEVEMENT MOTIVATION AS AN INTERVENING VARIABLE - Sri Rahayu; Bambang Satriawan; Nolla Puspita Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of compensation, workload, and organizational commitment on the performance of non-ASN state high school teachers in Batam City, with achievement motivation as an intervening variable. The background of the study is based on the phenomenon of low performance of some non-ASN teachers as indicated by the increasing proportion of performance assessments in the "sufficient" category from 24.0% in 2023 to 29.5% in 2024, which is thought to be influenced by low compensation, high workload, and weak organizational commitment. This study uses a quantitative approach with an explanatory research method. The study population was all 359 non-ASN state high school teachers in Batam City, using a saturated sampling technique. Primary data were collected through a Likert-scale questionnaire, while secondary data were obtained from official documents of the Riau Islands Provincial Education Office. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test the direct and indirect effects between variables. The results showed that compensation had a positive and significant effect on teacher performance and achievement motivation. Workload had a negative effect on performance, but not significant on achievement motivation. Organizational commitment has a positive and significant effect on performance and achievement motivation. Achievement motivation has a positive and significant effect on performance, while also mediating the relationship between compensation and organizational commitment on performance. However, achievement motivation does not mediate the effect of workload on performance. The implications of this study are the need for policies to increase appropriate compensation, manage proportional workloads, and strengthen organizational commitment to improve achievement motivation and the performance of non-civil servant teachers. This study is expected to serve as a reference for the Riau Islands Provincial Education Office in formulating human resource management policies in the education sector.